2005
DOI: 10.1111/j.0956-7976.2005.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Ironic Effects of Racial Bias During Interracial Interactions

Abstract: Previous research has suggested that Blacks like White interaction partners who make an effort to appear unbiased more than those who do not. We tested the hypothesis that, ironically, Blacks perceive White interaction partners who are more racially biased more positively than less biased White partners, primarily because the former group must make more of an effort to control racial bias than the latter. White participants in this study completed the Implicit Association Test (IAT) as a measure of racial bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
159
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(167 citation statements)
references
References 30 publications
5
159
2
1
Order By: Relevance
“…More egalitarian behavior results from less biased associations. Others have suggested that positive intergroup interactions flow from people's efforts to control their behavior during interactions (Shelton et al, 2005). Still others have proposed that automatically activated associations and behavioral regulation interact to influence behavior in intergroup settings (Dasgupta & Rivera, 2006;Fazio & Towles-Schwen, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More egalitarian behavior results from less biased associations. Others have suggested that positive intergroup interactions flow from people's efforts to control their behavior during interactions (Shelton et al, 2005). Still others have proposed that automatically activated associations and behavioral regulation interact to influence behavior in intergroup settings (Dasgupta & Rivera, 2006;Fazio & Towles-Schwen, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, approaches that treat implicit attitude measures as pure reflections of automatic associations would conclude that stronger associations predict disliking. The negative relationship between GNAT bias scores and likeability might also be used to refute the importance of self-regulation, as those who are presumed to regulate the most (i.e., those with higher implicit measure bias scores; Shelton et al, 2005) were liked the least. In contrast, our Quad model findings indicate that biased associations alone do not jeopardize the quality of an intergroup interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals' expectations of the interaction may alter their behavior; therefore, the use of naive partners can lead to different dynamics than use of study personnel (Miller & Turnbull, 1986). For example, naive partners who are expecting to be treated with prejudice may engage in positive compensatory behaviors to try to counter that likelihood (e.g., , and those who are expecting to be viewed as prejudiced may try to allay that impression through their behavior (e.g., Apfelbaum et al, 2008;Shelton, Richeson, Salvatore, & Trawalter, 2005). On the other hand, if during the course of the interaction naive partners feel misjudged, they may naturally react more negatively than trained confederates, who may dampen their natural response because of instructions to remain neutral toward the participant.…”
Section: Study Personnel Versus Naive Partnersmentioning
confidence: 99%
“…This may be due to the decrease in self-presentational concerns that occurs with a more structured interaction (Avery et al, 2009). As a wealth of literature in the field suggests, individuals entering an interaction with a person of a different race may be concerned about how they will be perceived and treated, influenced both by stereotypes about the other person's group and meta-stereotypes about their own group (Mallett et al, 2008;Shelton, Richeson, Salvatore, & Trawalter, 2005;Vorauer, Hunter, Main, & Roy, 2000;Vorauer & Kumhyr, 2001;Vorauer et al, 1998). Despite a desire for positive social outcomes, many individuals may take a misguided approach to try to accomplish those goals (Apfelbaum et al, 2008).…”
Section: Contextual Factorsmentioning
confidence: 99%